2020
DOI: 10.1186/s12889-020-8381-x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes towards E-cigarette use in Lebanon and their associated factors

Abstract: Background: Despite the misconceptions regarding E-cigarettes (ECs), only a few studies have been conducted in the Middle East that focused on this topic. This study assesses the knowledge of and attitudes towards ECs in Lebanon, determines how these two measures are associated, and identifies the variables that explain each of these measures. Methods: A cross sectional study was conducted on a convenience sample of Lebanese pedestrians aged between 18 and 64 inclusive. A structured self-administered questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 40 publications
4
11
0
Order By: Relevance
“…Regardless the fact our study showed the medical students had statistically higher knowledge scores than those from non-medical programs, the mean scores from both groups was below 50% correct, suggesting illiteracy about e-cigarettes even among the most knowledgeable university students. Numerous studies in USA, Lebanon, Saudi Arabia and Thailand were consistent with our findings [3,20,21,26,52]. Thus, the needs to approach and communicate to college students in both medical and non-medical schools that any tobacco use behavior is harmful, regardless of the used tobacco products (e-cigarettes, cigarettes, and waterpipe), especially given the fact that e-cigarettes are found to be more addictive than traditional cigarettes [12].…”
Section: Plos Onesupporting
confidence: 84%
See 1 more Smart Citation
“…Regardless the fact our study showed the medical students had statistically higher knowledge scores than those from non-medical programs, the mean scores from both groups was below 50% correct, suggesting illiteracy about e-cigarettes even among the most knowledgeable university students. Numerous studies in USA, Lebanon, Saudi Arabia and Thailand were consistent with our findings [3,20,21,26,52]. Thus, the needs to approach and communicate to college students in both medical and non-medical schools that any tobacco use behavior is harmful, regardless of the used tobacco products (e-cigarettes, cigarettes, and waterpipe), especially given the fact that e-cigarettes are found to be more addictive than traditional cigarettes [12].…”
Section: Plos Onesupporting
confidence: 84%
“…Gupta and colleagues reported low awareness level of the side effects related to e-cigarette use [19]. Further, around 63% of Lebanese participants shown low level of knowledge about e-cigarettes [20]. Almutham and colleagues presented that even medical students had low level of knowledge about ecigarettes competitively [21].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the literature have mainly been based on online surveys targeted at EC website visitors, and little is known about the population of EC users in the Middle East. A very recent study in Lebanon investigated EC-related knowledge and attitudes among a cross-sectional sample [ 17 ]. However, despite the high prevalence of EC use in the region, no studies have assessed the practices of EC users in the Middle East.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with our findings, a study conducted in Lebanon also demonstrated that majority of the participants had ever thought about quitting cigarette smoking (72.5%). 4 Similarly, 66.2% of medical students have considered ceasing e-cigarette consumption in Saudi Arabia. 23 This can be contributed to the participants receiving a higher education levels, as college was the majority representing 70% in Saudi Arabia, 44.3% in Lebanon of all respondents.…”
Section: Discussionmentioning
confidence: 99%
“… 3 A study that has been conducted in the middle east, Lebanon portrayed a higher prevalence in participants that have perceived e-cigarette as less harmful to due to their lack of knowledge. 4 In contrast, a study was done in Saudi Arabia which demonstrated a higher awareness levels that contributed to a lower prevalence of regular e-cigarette smokers. 5 The availability and variety of flavours associated with addictive nicotine are other reasons that make e-cigarettes more likable.…”
Section: Introductionmentioning
confidence: 98%